The Business innovation: a research proposal - consulting for competitiveness in Aguascalientes, Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The current turbulent change, challenge companies to be more competitive in national and international level, a competitive factor is innovation, so that it can be developed to contain human talent, technology, knowledge, quality and financial resources. For the status of innovation in products / services, marketing and production performance, and the use of technology, a diagnosis was made exploratory, descriptive and correlational, using a self-administered questionnaire with the idea of creating a research proposal - consultancy in SMEs in Aguascalientes. Thus, the study's purpose was to make a diagnosis, in order to develop a proposal that seeks to promote the management and innovation in SMEs in Aguascalientes, by the ratio of research and consultancy, to generate new ideas into products and services that strengthen business and that in turn impact on firms' competitive levels Aguascalientes. Among the results it is argued that the innovation of new products is significantly related to their quality, market positioning, competitive advantage, training opportunities for employees, among others. After theoretical and empirical analysis, the proposal-generated model of innovation and application consulting.
Keywords: consulting; innovation; SMES; competitiveness; technological change